Internal and External Corporate Governance Mechanisms and Earnings Management: An International Perspective - Fatma Zehri; Inaam Zgarni (Journal of Accounting and Management Information Systems (JAMIS), 2020)
Research question: This research aims to: 1. Determine which corporate governance mechanisms are most relevant in constraining earnings management and 2. Explain whether differences in results found in previous literature are attributable to moderating effects related to the legal system (common vs civil law). Motivation: One research topic of interest in the last two decades has been the effect of corporate governance mechanisms on earnings management. Idea: This research constitutes an extension of the study conducted by Zgarni and Haloui (2016) whose subject matter deals with only two corporate governance mechanisms, audit committee and audit quality, whereas the present paper contribution consists of testing the relevance of the findings achieved by Zgarni and Haloui (2016) after three years of study. Data: The study is based on a meta-analysis of 75 studies, the research approach being derived from Hunter et al. (1982). Research Findings: The empirical results show that the board of directors, the audit committee and audit size are statistically significant in reducing earnings management. Our findings emphasize the need to explicitly consider the influences of legal and institutional settings when analyzing the interactions between corporate governance and earnings management. The issues discussed in this article should be relevant to improve the supervision of companies and mitigating the earnings management. Especially, we provide some interesting insights to stakeholders, government regulators, banks, academics and research professionals.
Keywords: M41; 650; corporate governance; audit committee; board of directors; audit quality; earnings management; meta-analysis